2012
DOI: 10.1103/physrevlett.108.148302
|View full text |Cite
|
Sign up to set email alerts
|

Packing Spheres Tightly: Influence of Mechanical Stability on Close-Packed Sphere Structures

Abstract: Many experiments and simulations of packings of monodisperse hard spheres report a dominance of the face-centered cubic structure in the hexagonally close-packed limit, even though it has no significant energetic or entropic gain over other close-packed configurations. Combining simulations and experiments, we demonstrate that a simple mechanical instability which occurs during the packing process may play an important role in selecting the face-centered cubic structure over other close-packed alternatives. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 17 publications
3
33
0
Order By: Relevance
“…Bubble-bubble and bubble-wall collisions are accounted for by a repulsive potential force depending on the distance vector between the respective surfaces, as proposed by Heitkam et al (2012). The force induced on bubble i by bubble j reads…”
Section: Methodsmentioning
confidence: 99%
“…Bubble-bubble and bubble-wall collisions are accounted for by a repulsive potential force depending on the distance vector between the respective surfaces, as proposed by Heitkam et al (2012). The force induced on bubble i by bubble j reads…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that close-packed structures form with equal probability. However, the FCC structure is mechanically more stable and less often destroyed in the continuing dynamical growth process, as newly arrived atoms impact upon the structure [53].…”
Section: Crystallisation Of the Lennard-jones Fluidmentioning
confidence: 99%
“…This has been attributed to a reduced mechanical stability of non-FCC structures: forces between neighbouring spheres are not transmitted in the same way in FCC and HCP packings, making HCP packings noticeably less stable [26].…”
Section: Wet Foams At the Rigidity Loss/jamming Transitionmentioning
confidence: 99%
“…This is particularly so for disordered samples, which require manually dealing with individual topological changes as liquid fraction is varied. Investigations close to the jamming transition commonly simulate the foam as a dense packing of spheres which interact via a pairwise potential [26,[51][52][53]71].…”
Section: Simulationsmentioning
confidence: 99%